Chinese young people's diverse experiences with heterosexual romantic relationships in various high school contexts. Issue 2 (June 2023) - Liu, Chong; Zhu, Yan
Young people's heterosexual romantic relationships is often a popular topic in youth studies and sexuality education. However, the importance of class and educational stratification and the institutional influence is rarely mentioned. Through this article, considering the differentiated expectation of young people in different high school categories and the discussion about sexuality education, young people are understanding and experiencing heterosexual romantic relationships beyond their individual level. Drawing on the fieldwork with 28 student participants and 7 schoolteachers in total at an academic high school and a vocational high school in Tianjin, China, this article unearths young people's considerations, decisions, and doubts concerning their experiences of heterosexual romantic relationships. It argues that young people's perceptions and experiences of heterosexual romantic relationships are highly diverse and complex. It calls for the awareness of intersectional factors, such as social class and gender, in the process of understanding such diversity and complexity.